2007
DOI: 10.1093/europace/eum161
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac resynchronization therapy: left or left-and-right for optimal symptomatic effect the LOLA ROSE study

Abstract: In this pilot study, we found no differences in major clinical outcome measures between the two modes of resynchronization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Several studies have demonstrated that biventricular pacing and LV‐only pacing are similar in terms of acute haemodynamic response, chronic echocardiographic response, exercise capacity, quality of life, and mortality and hospitalization rates . However, in these studies, patients were not generally selected based on the existence of normal AV conduction, and LV activation was not specifically timed to be synchronized with intrinsic RV conduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that biventricular pacing and LV‐only pacing are similar in terms of acute haemodynamic response, chronic echocardiographic response, exercise capacity, quality of life, and mortality and hospitalization rates . However, in these studies, patients were not generally selected based on the existence of normal AV conduction, and LV activation was not specifically timed to be synchronized with intrinsic RV conduction.…”
Section: Discussionmentioning
confidence: 99%
“…Although cardiac resynchronization therapy (CRT) utilizing biventricular pacing has become a well‐established treatment for heart failure (HF) patients with low LV ejection fractions (LVEF) and conduction abnormalities, it is possible that LV‐only pacing with intrinsic RV activation may result in greater improvements in cardiac function. Several studies have demonstrated that LV‐only pacing is non‐inferior to biventricular pacing in HF patients indicated to receive CRT . Smaller studies have also suggested that LV‐only pacing, when timed to coincide with native RV activation, may result in more synchronous electrical activation and superior RV and LV function compared with biventricular pacing.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 4 studies were not RCTs, 4 studies did not report outcomes of interest, 8 studies had different interventions, and 2 studies were excluded for being a study protocol ( Figure 1 ). Of the 14 RCTs which were included in the final analysis, six were cross-over trials [ 19 , 21 , 28 31 ]. Three RCTs compared the effect of TriV to that of BiV [ 23 , 29 , 30 ], and the sample size ranged from 18 to 306 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of studies demonstrated that BiV pacing was associated with superior outcomes compared to conventional CRT [ 32 ], LUV pacing [ 33 ], and RUV pacing in patients without advanced HF [ 34 ], other studies reported no significant difference in improvement in NYHA scores and reverse remodeling between patients who received BiV pacing and those who received LUV pacing [ 20 , 21 ], as well as between those who received BiV pacing and those who received RUV pacing [ 28 ]. Additionally, patients who failed to respond to BiV pacing responded to LUV pacing [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation